Terapi Musik sebagai Terapi Komplementer untuk Menurunkan Kecemasan Pasien - Yuliasih Yuliasih; Sri Yona; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of music therapy in reducing anxiety in patients in the intensive care unit. The research method uses article searches conducted on four databases, namely Science Direct, Embase, Pubmed, and Proquest, with the keywords